Managing global financial and foreign exchange rate risk - Homaifar, Ghassem (Hoboken, N.J. : J. Wiley, 2004)
A comprehensive guide to managing global financial risk from the balance of payment exposure to foreign exchange and interest rate risk, to credit derivatives and other exotic options, futures, and swaps for mitigating and transferring risk, this book provides a simple yet comprehensive analysis of complex derivatives pricing and their application in risk management.
Includes bibliographical references (p. 365-372) and index.
oif 31/08/15
Loan
Keywords: Foreign exchange rates; Foreign exchange; Risk management; Foreign exchange rates - United states